Determinants on Performance of Junior High School Teachers with Work Motivation as Mediation - Muna, Lina Fauzul; Rusdarti, Rusdarti; Yusuf, Amin (Educational Management, 2020)
The role of the teacher becomes an interesting topic to discuss, no exception related to performance. Teacher performance is related to the success of teachers in carrying out their duties and obligations. However, many factors affect teacher performance. This study aims to examine and analyze teacher performance with various factors that influence it. The method used is quantitative. The population was all 911 state junior high school teachers in Kudus Regency. The number of samples was 186 teachers. Data was collected through a questionnaire that has been tested for validity and reliability. Furthermore, the data were analyzed using path analysis by SPSS program and the Sobel test to assess mediation variables. The results showed that: first, the influence of the principal's leadership, teacher commitment and emotional intelligence of teachers to work motivation is accepted; second, the influence of school principal leadership, teacher commitment and emotional intelligence of teachers on teacher performance through work motivation is accepted; and third the influence of work motivation on teacher performance is accepted. Work motivation has also been proven to be able to mediate the influence of school principal leadership, teacher commitmen and emotional intelligence of teachers on teacher performance. The performance of state junior high school teachers in Kudus in carrying out their duties and obligations is influenced by a number of factors including school principal leadership, commitment, teacher emotional intelligence and work motivation. It is recommended that teachers can maintain and even increase commitment and understanding and management of emotions so that it can have an impact on the performance of each teacher.